(untitled) (SCIENCE TIME JOURNAL, 2025)
Urolithiasis is one of the most common diseases encountered in urological practice and represents an essential topic in undergraduate and postgraduate medical education. Effective teaching of this condition requires not only strong clinical content but also the use of modern pedagogical technologies to enhance students’ learning outcomes. This article aims to analyze and improve the application of contemporary pedagogical technologies in teaching urolithiasis within the discipline of urology. The study highlights the effectiveness of interactive methods, digital learning tools, simulation-based training, and problem-based learning in improving students’ clinical reasoning, engagement, and practical skills. The integration of modern educational technologies contributes to higher academic achievement and better preparedness for clinical practice.